2020
DOI: 10.21203/rs.3.rs-118913/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What validation tests can be done by the clinical medical physicist while waiting for the standardization of quantitative SPECT/CT imaging?

Abstract: Objective The aim of the study was to assess the accuracy of quantitative SPECT/CT imaging in a clinical setting and to compare test results from two nuclear medicine departments.Methods Phantom studies were carried out with two gamma cameras manufactured by GE Healthcare: Discovery NM/CT 670 and NM/CT 850, used in two nuclear medicine departments.Results The convergence of activity concentration recovery was validated for the two gamma cameras operating in two medical centres using a homogeneous 3D phantom. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The variation between centres is mainly caused by the use of different reconstruction algorithms and/or settings. Based on their research, the authors confirmed that the OSEM iterative method with 5 iterations and 15 subsets, without the 3D post-reconstruction filter, is the optimal clinical method for the reconstruction of quantitative images obtained with the NM/CT850 gamma camera [21,12]. On the other hand, for the gamma camera Symbia Intevo, Gnesin et al [2] chose the iterative reconstruction technique with 16 iterations and 4 subsets and Gaussian smoothing of FWHM 7.5 mm (for foci with a diameter greater than 24 mm) as the optimal method.…”
Section: Reviewmentioning
confidence: 88%
“…The variation between centres is mainly caused by the use of different reconstruction algorithms and/or settings. Based on their research, the authors confirmed that the OSEM iterative method with 5 iterations and 15 subsets, without the 3D post-reconstruction filter, is the optimal clinical method for the reconstruction of quantitative images obtained with the NM/CT850 gamma camera [21,12]. On the other hand, for the gamma camera Symbia Intevo, Gnesin et al [2] chose the iterative reconstruction technique with 16 iterations and 4 subsets and Gaussian smoothing of FWHM 7.5 mm (for foci with a diameter greater than 24 mm) as the optimal method.…”
Section: Reviewmentioning
confidence: 88%